Common pediatric medical procedures. Leg exam, knee and ankle - Baum, Rebecca; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2018)
A complete review and demonstration of the examination for knee and ankle pathology, including positioning techniques and assessment.
Presenter: Rebecca Baum.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Knee -- Diseases -- Diagnosis; Ankle -- Diseases -- Diagnosis; Leg -- Examination; Knee -- Examination; Ankle -- Examination; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films